Synthesis and characterization of new biodegradable polymers and study of some properties in phosphate buffers - Khalf, Husein N.; Swaadi, Ali K.; Muhseen, Raheem J. (Iraqi Journal of Aquaculture, 2022)
Copolymers between polylactic acid and polyethylene glycol, also alganic acid and polyethylene glycol were synthesized and disocynate (MDI) were prepared and characterized. Swelling behaviors and loss of weight of these polyurethanes were studied by immersion of the gels in various buffer solutions. Particularly the polyurethane foam showed the highest EWC (equilibrium water constant) in timedependent and pH-dependent swelling.